Implementasi Wakaf Produktif dan Wakaf Tunai Di Indonesia - Barmawi Mukri (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Actually, the property donated for religious foundation is one of the economical potential that is can be applied on overcoming the economical crisis and it is for human kind prosperity Ifitis regulated professionally and productively. For instance, the donated landcan be funded the buildings for rent or the amount of money that is invested for profit interest with the regard of legality.